Milk fatty acid composition of unsupplemented dairy cows grazing on a tropical pasture - Dias K.M.* (2019)
© This is an open access article distributed under the terms of the Creative Commons Attribution License.This study aimed to evaluate the milk fatty acid (FA) composition of unsupplemented dairy cows grazing on elephantgrass (Pennisetum purpureum Schum. cv. Pioneiro) pastures under three grazing management strategies: pre-grazing height of 120 cm with defoliation intensities of 50 and 70% of the initial height (treatments 120/50 and 120/70) and pre-grazing height of 90 cm with defoliation intensity of 70% (treatment 90/70). Treatments were repeated three times in a complete randomized block design. Tester animals were six multiparous Holsteins cows grouped into pairs according to days in milk and milk yield and allocated to blocks. Individual milk samples were collected after the first and second days of grazing (two-day occupation period) and analyzed for FA composition. Milk fat from 120/50 and 90/70 treatments resulted in higher concentrations of C4:0, C6:0, C17:0 anteiso, rumenic acid (RA), vacenic acid (VA), trans-12 C18:1, trans-13/14 C18:1, cis-11 C18:1, cis-12 C18:1, cis-9, trans-12 C18:2, trans-11, cis-15 C18:2, and total polyunsaturated fatty acids. Additionally, both SCD14 (cis-9 14:1/14:0 + cis-9 14:1) and SCDRA (RA/VA + RA) desaturase indices were reduced in milk fat from cows subjected to 120/50 and 90/70 treatments. On average, the milk fat levels of RA and VA observed in our study were greater than those reported in most studies with tropical grass-based diets and similar to levels usually found in cows grazing on temperate pastures. Overall, our results showed that milk with a desirable fatty acid composition is produced by cows grazing on a tropical grass (elephantgrass cv. Pioneiro), with the combination of a pre-grazing height of 120 cm and a defoliation intensity of 50% of the initial height, being a practical management strategy to achieve this goal.